E?cacy of Ultrasound Intrinsic Compression Strain Elastography in Prediction of Malignancy in Thyroid Nodules with Fine Needle Aspiration Cytology Correlation - Rapelli Ramakrishna; Madhavi Thatipamula (Asian Journal of Medical Radiological Research, 2020)
Background: Different diagnostic modalities are used to evaluate and diagnose efficiently thyroid nodules. These include Clinical Examinations, Thyroid Function Test (TFT), Scintiscan, Ultrasonography (USG), Fine Needle Aspiration Cytology (FNAC), and Histopathological examination. However, clinical assessment, TFT and USG have been poor parameters for assessing thyroid nodules. The objective is to this study was aimed to evaluate the efficacy of Ultrasound Elastography for the prediction of malignancy in thyroid nodule. Subjects and Methods:After obtaining written informed consent, demographic data such as age, sex and clinical features like, swelling, mode of onset, difficulty in swallowing, difficulty in breathing, hoarseness of voice obtained through an interview and recorded on predesigned and pretested proforma (Annexure II). Further these patients were subjected Grayscale Ultrasound, Ultrasound Elastography and FNAC. Results: Malignant lesions were noted in 19 patients on FNAC. Among them, 16 (84.21%) patients had malignant lesions while 3 (15.79%) patients had benign lesions based on combined USE and ECI criteria. This difference was statistically significant (p<0.001). The sensitivity of combined USE and ECI criteria in the diagnosis of malignant lesions was 84.21% with Specificity of 81.69%, PPV 55.17% and NPV 95.08%. Conclusion: Based on the findings of this study it may be concluded that, USE as determined by the Ragos criteria, TI RADS score are highly associated with malignant thyroid lesions and useful in differentiating the malignant thyroid lesions from benign ones.